IEEE InternationalElectron Devices Meeting, 2005. IEDM Technical Digest.
DOI: 10.1109/iedm.2005.1609459
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-doped gesbte phase-change memory cells featuring 1.5 V/100-μA standard 0.13μm CMOS operations

Abstract: We demonstrated the operation of phase-change memory cells that enabled 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 7 publications
1
64
0
Order By: Relevance
“…13) and in oxygen doped memory cells (Matsuzaki et al, 2005). Moreover, increase of the crystal grain size has been also reported in 6 at.…”
Section: Wwwintechopencommentioning
confidence: 95%
“…13) and in oxygen doped memory cells (Matsuzaki et al, 2005). Moreover, increase of the crystal grain size has been also reported in 6 at.…”
Section: Wwwintechopencommentioning
confidence: 95%
“…Some of them can also suppress the GST grain growth as well as enhance its thermal stability. [7,11,12,[14][15][16] In addition, it has been reported that doping boron is also favorable for the optical and electrical properties of Ge-Sb-Te ternary alloys. [17][18][19] Nevertheless, thus far most studies have focused on incorporating impurities into phase change materials using the reactive magnetron cosputtering technique.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies have proved that doping impurities is an effective way to optimize the intrinsic properties of GST. For example, incorporation of elements such as nitrogen, [7][8][9][10][11][12] oxygen, [11][12][13][14] and silicon [15,16] into GST indeed increases the GST resistivity, thus reducing the programming current. Some of them can also suppress the GST grain growth as well as enhance its thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it can be miniaturized easily. Most commonly used materials for PCRAM are Ge 2 Sb 2 Te 5 and Sb 2 Te 3 but materials doped with impurities such as nitrogen or oxygen also have been studied to improve operation speed or thermal stability [22,23,24,25]. The operating principle of PCRAM is based on the phase change of chalcogenide material from amorphous to crystal, or vice versa, at reasonably low temperature around 600 C [26].…”
Section: Pcrammentioning
confidence: 99%